TAXES AND ALMS SEEN FROM ISLAMIC LAW - Mohammad Solekhan; Gunarto Gunarto (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
State need expense to construction and welfare their people, for that the state revenue are needed. In Islamic law there are revenue that can be done through alms and taxes. But in the tax collection implementation, Islamic law had been giving a clear guidance either for Muslims or non Muslims. According to the scholars, the tax collection are allowed of it fulfill three criteria, that is: (1) taxes because to fund expenditure that are really needed to realized Maqasid Syariah; (2) the tax burden should not be to stiff to everyone capable to pay; (3) tax funds that has been collected are spent honestly for a good cause. There is a responsibility for Muslims to pay taxes if the treasury fund need it or empty. Those responsibilities are as a devotion to ulil amri, as stated in An-Nisa letter verse 59, which means: “O believer, obey Allah and obey his Prophets and ulil amri amongst you. Then if you different in opinions about something, then give him him back to Allah (Al quran) and Prophet (his Sunnah), if you truly faithful to Allah and for the next day. That is more important (to you) and better for it cause” Keywords: Taxes, Alms, Islamic Law